Relativity and Singularities - A Short Introduction for Mathematicians (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We summarize the main ideas of General Relativity and Lorentzian geometry, leading to a proof of the simpIest of the ceIebrated Hawking-Penrose singularity theorems. The reader is assumed to be familiar with lliemannian geometry and point set topology.